Dissolution : the Crisis of Communism and the End of East Germany. - Maier, Charles S. (Princeton University Press, 2001)
Against the backdrop of one of the great transformations of our century, the sudden and unexpected fall of communism as a ruling system, Charles Maier recounts the history and demise of East Germany. Dissolution is his poignant, analytically provocative account of the decline and fall of the late German Democratic Republic. This book explains the powerful causes for the disintegration of German communism as it constructs the complex history of the GDR. Maier looks at the turning points in East Germany's forty-year history and at the mix of coercion and consent by which the regime functioned. He.